STUDI PENGGUNAAN KALSIUM KARBONAT ATAU TRIKALSIUM FOSFAT DAN KONSENTRASI AGAR TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SOYGURT BERKALSIUM TINGGI - Josaphat, Grace Evekyn; Kuswardani, Indah; Suprijono, Maria Matoetina (Widya Mandala Surabaya Catholic University, 2014)
Soymilk has beany flavor and lack of calcium content which can be improved by fermentation of soymilk becoming set soygurt and calcium fortification using calcium carbonate or tricalcium phosphate. The differences of calcium salts may affect the soymilk colloid system, therefore it needs a stabilizer, for example agar. Then, a study of the use of calcium salts and appropriate agar concentration to produce a high calcium set soygurt is needed. The experimental was Randomized Block Design using factor Agar Concentrations on (A): 0,0% (0); 0,1% (1) and 0,2% (2) nested to the of Calcium Salts: Calcium Carbonate (C) and Tricalcium Phosphate (F). Parameters observed were syneresis, calcium content, and sensory characterisitics (preferences to texture and taste of the soygurt). The complement analysis were pH, acidity and protein content of soygurt. The data were analyzed using ANOVA at Î± = 5%, continued by DMRT test to determine the level of treatment that gives the significant effects. The result show significant difference of agar concentrations nested to the calcium salts gave significant effects to texture & taste of soygurt, but no siginificant effect to calcium content and syneresis of soygurt. Soygurt with 0,0% concentration of agar gave the highest score of texture preference at both kind of calcium salts. Agar concentration at 0,1% and 0,2% gave no significant difference on texture. Kind of calcium salts gave significant effect on taste preference on which soygurt with Tricalcium Phosphate gave higher score than Calcium Carbonate. The preference of taste of soyghurt treated with Tricalcium Phosphate was higher than The Calcium Carbonate, showed by score 4.3-4.4 compared to 3.2-3.8, on scale 1-7.